2020
DOI: 10.1183/13993003.02096-2019
|View full text |Cite
|
Sign up to set email alerts
|

CAMPHOR score: patient-reported outcomes are improved by pulmonary endarterectomy in chronic thromboembolic pulmonary hypertension

Abstract: BackgroundPulmonary endarterectomy (PEA) is the recommended treatment for eligible patients with chronic thromboembolic pulmonary hypertension (CTEPH). The Cambridge Pulmonary Hypertension Outcome Review (CAMPHOR) score is an internationally-validated patient-reported outcome (PRO) measure for CTEPH. It assesses 3 domains: activity, quality of life (QoL) and symptoms. We assessed PROs in patients with CTEPH undergoing PEA.MethodsThis retrospective observational study of consecutive CTEPH patients undergoing PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
63
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(71 citation statements)
references
References 41 publications
4
63
1
3
Order By: Relevance
“…(3, 23, 24) Studies exploring differences in HRQoL between patients with CTEPH and IPAH have mixed results with some finding no difference and others showing CTEPH patients having worse HRQoL. (13,25,26) The results from this study demonstrate that patients with CTEPH have worse HRQoL at referral to a Pulmonary Hypertension Care Center as compared to patients with IPAH, but these differences do not persist over time in a large prospective multicenter cohort. Among CTEPH patients, similar to what has been previously reported, (26) this study found that patients who undergo PTE have significant improvement in their HRQoL, and the improvement in scores may be more significant in patients without residual disease post-PTE.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…(3, 23, 24) Studies exploring differences in HRQoL between patients with CTEPH and IPAH have mixed results with some finding no difference and others showing CTEPH patients having worse HRQoL. (13,25,26) The results from this study demonstrate that patients with CTEPH have worse HRQoL at referral to a Pulmonary Hypertension Care Center as compared to patients with IPAH, but these differences do not persist over time in a large prospective multicenter cohort. Among CTEPH patients, similar to what has been previously reported, (26) this study found that patients who undergo PTE have significant improvement in their HRQoL, and the improvement in scores may be more significant in patients without residual disease post-PTE.…”
Section: Discussionmentioning
confidence: 68%
“…(13,25,26) The results from this study demonstrate that patients with CTEPH have worse HRQoL at referral to a Pulmonary Hypertension Care Center as compared to patients with IPAH, but these differences do not persist over time in a large prospective multicenter cohort. Among CTEPH patients, similar to what has been previously reported, (26) this study found that patients who undergo PTE have significant improvement in their HRQoL, and the improvement in scores may be more significant in patients without residual disease post-PTE. (4,5) The worse HRQoL observed in CTEPH patients at referral was not explained by older age as compared to IPAH patients; however, older age may be associated with increased co-morbid conditions, which were not available for us to account for.…”
Section: Discussionmentioning
confidence: 70%
“…To the authors' knowledge, the only published PRO instruments for PH that assess both symptoms and impacts and whose validation work included patients with CTEPH are the Cambridge Pulmonary Hypertension Outcome Review (CAMPHOR) [8] and the emPHasis-10 [9]. The CAMPHOR assesses symptoms, functioning, and HRQoL, and has been used to measure the symptoms and impacts of CTEPH [7]. However, the instrument includes 65 items [8,10], which could make it challenging to administer in both real-world clinical practice and clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Patient-reported outcome (PRO) instruments are useful in evaluating CTEPH symptoms and their impact on patients’ daily lives and general wellbeing [ 6 ]. However, the limited number of clinical trials on CTEPH have not generally assessed HRQoL as an outcome, so there is little data pertaining to these outcomes in patients with CTEPH [ 6 , 7 ]. Those studies that have assessed HRQoL in patients with CTEPH have used PRO instruments that are either generic (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation